Earth care : world folktales to talk about - MacDonald, Margaret Read, 1940- (August House Publishers, 2005)
A collection of traditional tales and proverbs from thirty countries or ethnic groups that covers topics on the environment, wildlife, nature, and man's relationship with the earth.